Dynamics of the Development of Philosophy of Science and Its Implications for Contemporary Management Theory - Irawan, Risky (Riwayat: Educational Journal of History and Humanities, 2025)
The development of science in the 21st century has undergone significant transformations not only in the empirical and technical domains but also in conceptual and philosophical dimensions. Philosophy of scienceconcerned with ontology, epistemology, and axiologyhas experienced dynamic shifts shaped by globalization, digitalization, and technological acceleration. These developments have had strong implications for contemporary management theory, which must address increasing complexity, ambiguity, and ethical challenges. This study aims to analyze the dynamics of philosophy of science in the last decade and their influence on management theory, with particular attention to leadership, innovation, ethics, and sustainability. Using a qualitative literature study, the research draws upon scholarly articles, books, and conference papers to construct a conceptual framework. Findings indicate four major transformations: (1) ontology has moved from positivist and mechanistic views toward complexity and context-dependence; (2) epistemology has shifted to pluralism, acknowledging the legitimacy of multiple methods; (3) axiology has increasingly emphasized value-laden inquiry, recognizing the ethical and social dimensions of scientific practice; and (4) technological advancement, particularly in artificial intelligence and data-driven systems, has challenged conventional standards of knowledge, fairness, and accountability. These philosophical shifts demand that management theory evolve into a more adaptive, value-sensitive, and contextually grounded practice. Practical illustrations, including responses to the COVID-19 pandemic and algorithmic bias in recruitment, demonstrate how philosophy of science can enrich managements responsiveness to global and local challenges. Ultimately, this study highlights the importance of philosophical literacy in sustaining management theorys relevance in contemporary contexts.